2013
DOI: 10.1097/jto.0b013e31829f684a
|View full text |Cite
|
Sign up to set email alerts
|

Association of Exon 19 and 21 EGFR Mutation Patterns with Treatment Outcome after First-Line Tyrosine Kinase Inhibitor in Metastatic Non–Small-Cell Lung Cancer

Abstract: Different subtypes of EGFR exon 19 and 21 mutations exhibited differential survival to first-line TKI therapy. Detailed sequence evaluation of exon 19 deletions may provide important prognostic information on survival outcome after TKI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
106
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(116 citation statements)
references
References 29 publications
6
106
3
Order By: Relevance
“…is already approved in advanced NSCLC (Alimujiang et al, 2013;Aydiner et al, 2013;Lee et al, 2013;Zhang et al, 2011). Anaplastic lymphoma kinase (ALK) gene is one of the most important issues in targeted therapy.…”
Section: Introductionmentioning
confidence: 99%
“…is already approved in advanced NSCLC (Alimujiang et al, 2013;Aydiner et al, 2013;Lee et al, 2013;Zhang et al, 2011). Anaplastic lymphoma kinase (ALK) gene is one of the most important issues in targeted therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, investigators have demonstrated that EGFR mutations, especially the deletion mutation delE746-A750 in exon 19 and the substitution mutation (L858R) in exon 21, were associated with gefitinib sensitivity of NSCLC patients (24). In 170 NSCLC patients with different EGFR mutations, those patients with EGFR mutations in exon 19 exhibited significantly longer progression-free survival (12.8 months) than those with mutations in exon 21 (10.6 months) (25). The finding supported the hypothesis that EGFR mutations in exon 19, especially delE746-A750, was more effective in predicting TKI sensitivity (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…30 Patients harboring delE746 demonstrated better median PFS (14.2 months) than those harboring delL747 (6.5 months; p = 0.021). 30 A retrospective study obtained the same outcome, revealing that median PFS of delE746 was significantly longer than delL747 (11.7 vs 10.0 months, respectively; p = 0.022). 31 In addition, 21L858R derived a longer median PFS than L861R/L861Q (11.4 vs 2.1 months, respectively; p = 0.034).…”
Section: Different Locations In Egfr Tk Domain and Uncommon Sensitivementioning
confidence: 99%
“…31 In addition, 21L858R derived a longer median PFS than L861R/L861Q (11.4 vs 2.1 months, respectively; p = 0.034). 30 In a retrospective study, examining predictors of EGFR-TKI response in EGFR-mutant NSCLC patients, common mutations (19del and 21L858R) were found to be independent predictors of better treatment outcome (vs minor mutations, including mutations in exons 18 and 20 and unusual mutations occurring in exons 19 and 21; median PFS: 12.5 vs 4.3 months, respectively; p = 0.022). 32 However, the outcomes of this study should be interpreted with caution as mutations in exons 18 and 20 may represent a resistant, instead of a sensitive, mechanism to EGFR-TKIs.…”
Section: Different Locations In Egfr Tk Domain and Uncommon Sensitivementioning
confidence: 99%